2018
DOI: 10.2174/1389450118666170704132523
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Polymer-based Wound Dressings for the Treatment of Diabetic Foot Ulcer: An Overview of State-of-the-art

Abstract: In summary, this review enlightens the most recent developments in polymer-based wound dressings with special emphasis on advanced polymeric biomaterials, innovative therapeutic strategies and delivery approaches for the treatment of DFUs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
95
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(97 citation statements)
references
References 0 publications
2
95
0
Order By: Relevance
“…Bioactive wound dressings generally comprise antimicrobial dressings (Alavi et al, ; Marston, Tang, Kirsner, & Ennis, ), drug‐released dressings (Jull et al, ; Stana et al, ), and nutrition‐providing dressings (Ray & Kalia, ). Recently, Hussain et al systematically reviewed and reported a number of convincing evidences for bioactive materials embedded polymer‐based chronic wound healing modalities, as well as the latest and innovative therapeutic strategies for management of chronic nonhealing wounds (Hussain, Thu, Shuid, Katas, & Hussain, ; Shao et al, ). Related studies also introduced technical solutions in development of different biomaterials used in wounds healings (Mir et al, ; Murray, West, Cowin, & Farrugia, ; Pop & Almquist, ).…”
Section: Polymer‐based Functional Wound Dressings For Treating CVImentioning
confidence: 99%
“…Bioactive wound dressings generally comprise antimicrobial dressings (Alavi et al, ; Marston, Tang, Kirsner, & Ennis, ), drug‐released dressings (Jull et al, ; Stana et al, ), and nutrition‐providing dressings (Ray & Kalia, ). Recently, Hussain et al systematically reviewed and reported a number of convincing evidences for bioactive materials embedded polymer‐based chronic wound healing modalities, as well as the latest and innovative therapeutic strategies for management of chronic nonhealing wounds (Hussain, Thu, Shuid, Katas, & Hussain, ; Shao et al, ). Related studies also introduced technical solutions in development of different biomaterials used in wounds healings (Mir et al, ; Murray, West, Cowin, & Farrugia, ; Pop & Almquist, ).…”
Section: Polymer‐based Functional Wound Dressings For Treating CVImentioning
confidence: 99%
“…A versatile range of naturally-originated polymers including chitosan, hyaluronic acid, cellulose, alginate, dextran, collagen, gelatin, elastin, fibrin, and silk fibroin has been developed as wound dressings recently. 46 These polymers have been used in the form of hydrogels, films, hydrocolloids, foams, membranes, scaffolds, micro-particles, and nano-particles for wounds and can play a role in wound exudate management, while at the same time enhancing wound healing by delivery of essential wound modulatory peptides and anti-bacterial drugs. Chitosan is the newest naturally occurring polymer that has been potentially developed into forms of dressings that can deliver inflamation regulatory peptides such as neurotensin to accelerate wound healing.…”
Section: Developing New Dressing Technologiesmentioning
confidence: 99%
“…Gelatin is a collagen derivative and is applicable to wounds that need a more hydrogel-like material. It is biocompatible and degradable in physiological medium and can mimic many of the characteristics of the dermis [40]. A research group that used bFGF-impregnated gelatin microspheres found that gelatin stimulates angiogenesis and fibroblast proliferation [41].…”
Section: Figurementioning
confidence: 99%
“…Hyaluronic acid (HA) presents a wide range of natural healing properties such as tissue integrity, lubrication, and water absorption. Similar to collagen, HA promotes mesenchymal and epithelial cell migration and differentiation, ultimately improving collagen deposition and angiogenesis for repair [40]. HA's properties are sensitive to molecular weight, however.…”
Section: Hyaluronic Acidmentioning
confidence: 99%
See 1 more Smart Citation